Menstrual cycle and workplace issues: review of the literature - Fitzgerald, Kimberly (2016)
Physical and emotional symptoms relating to the menstrual cycle can have different effects for different women. For women who experience extreme symptoms, such as pain, heavy bleeding and mood disruptions, symptoms may have an impact on functioning at work. Health practitioners may need to make special considerations when working with women who experience menstrual disorder symptoms. This article explores relevant articles related to menstrual disorders and the workplace. Various topics are covered with a special focus on occupational health considerations. Menstrual cycle studies have mostly focused on quantitative research and have largely neglected the importance of women’s subjective experiences. This article identifies that most studies have overlooked such issues up to date, and provides an overview of reasons why more mixed methods research should be conducted on menstrual cycle studies. Women’s subjective experiences are often overlooked. Women who experience imposing menstrual cycle symptoms would benefit from person-centred treatment interventions.